Réponses

2013-05-15T18:38:24+02:00

a= (x-5) (x-7)

a = x² -7x -5x +35

a = x² -12x +35

 

b=(y+-2) (y-3)

b = y² -3y -2y -6

b= y² -5y -6

 

c=(4x-1) (x-5)

c= 4x² -20x -x +5

c= 4x² - 21x +5

 

d=(5y-2)(y-3)

d= 5y² -15y -2y +6

d= 5y² -17y +6

Meilleure réponse !
2013-05-15T18:45:15+02:00

 

 

a= x²+-7x-5x+42

   = -13x + x²+42

 

b=y²-3y-2y+6

  =-5y+y²+6

 

c=4x²-20x-1x+5

 = -21x+4x²+5

 

d=5y²-15y-2y+6

  =-17y+5y²+6

 j'ai compris qu'il fallait faire ca après j'èspère t'avoir aidé:)